Evaluation of pulp and paper properties produced from two new bleaching sequences - Rodrigues De Oliveira, Cláudia [UNESP]; Ventorim, Gustavo [UNESP]; Rodrigues De Oliveira, Iliane [UNESP]; Ferraz, Ana Paula Almeida [UNESP]; Silva, Luana Cristal Lirya [UNESP]; Nunes Dos Santos, André Luis [UNESP] (De Gruyter, 2022)
The pulp and paper industry is increasingly seeking a sustainable and conscientious development, minimizing the environmental impacts caused by it. Therefore, reducing efficiently the number of stages used in the bleaching process can mean less consumption of water and chemical reagents, contributing to the reduction of harmful waste to the environment. Thus, this study sought to evaluate the pulp quality and some physical-mechanical properties (smoothness, tear and tensile indexes) of two new bleaching sequences A∗DP and A∗E∗DP and compare them with the reference D0(E+P)D1P. To do so, industrial eucalyptus Kraft pulp pre-delignified with oxygen was used. The bleached pulp was refined to 1200, 1800 and 2400, in PFI mill and tested according to TAPPI standards to determine smoothness, tear and tensile indexes. Based on the results obtained, it was verified that the sequences studied are viable for using in bleaching plants, which allowed a reduction in the chlorine dioxide consumption and presented satisfactory smoothness, tear and tensile indexes for paper.
Keywords: bleaching; paper; pulp; tear index; tensile index